Utilization of Shrimp Shell Meal Containing Chitosan as a Source of Prebiotic in Preweaned Crossbred Piglets - Kumar, M. Yugandhar; Ramana, J.V.; Ravi, A.; Suresh, J.; Sivakumar, A.V.N. (Indian Journal of Animal Nutrition, 2018)
The effect of inclusion of antibiotic or chitosan from shrimp shell meal (SSM) as prebiotic in the diet was evaluated using 240 pre-weaned piglets (10 d of age). The standard creep ration (T1) was supplemented with chlorotetracyclin (T2) while SSM was included at 0.5 (T3), 1.0 (T4) and 1.5% (T5) level as a source of chitosan. Each treatment consisted of 6 pens with 8 piglets per pen. The animals were provided with feed and water ad lib. during the experiment for 42 days. Higher (P